Generic and biosimilar medicines: quid? - Simoens, Steven (Farmeconomia. Health Economics and Therapeutic Pathways, 2012)
Once intellectual property protection, data and marketing exclusivity of reference medicines have expired, generic medicines and biosimilar medicines can enter the off-patent market. This market entry is conditional on the approval of marketing authorization, pricing and reimbursement. Given that there tends to be confusion surrounding generic and biosimilar medicines, this Editorial introduces basic concepts related to generic and biosimilar medicines and presents the different studies and articles included in this supplement dedicated to generic and biosimilar medicines.